Economic, societal, and environmental evaluation of woody biomass heat utilization: A case study in Kobe, Japan. (April 2022) - Zhou, J.; Tabata, T.
Abstract: This study aims to develop a model for the integrated evaluation of woody biomass heat utilization considering the environment, economy, and society. Herein, a woody biomass heat utilization business was virtually operated at Mt. Rokko, Kobe, Japan. In the societal impact assessment, a questionnaire survey was conducted to clarify tourist opinions regarding the hypothetical hot bath facility, and its societal value was estimated using the contingent valuation method. The total benefit estimated based on the willingness to pay was 5.92 million USD. In the economic evaluation, an economic model was constructed using life cycle cost. If kerosene was added to the wood chips, the optimum scale of the wood chip boiler installed was 687 kW, and the fossil fuel substitution rate reached 95.9%. The difference between the annual cost was −126.74–100.12 thousand USD. In the environmental impact assessment, a life cycle assessment was conducted to clarify how the use of woody biomass heat may change the environmental impact of the hypothesized hot bath facility. The net greenhouse gas emissions per 1 GJ were −69.9 kg-CO2eq /GJ in kerosene.